TARI TUMBU TANAH SEBAGAI JATI DIRI MASYARAKAT SUKU ARFAK DI MANOKWARI, PAPUA BARAT - Iwan Dwi Aprianto (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
Tumbu Tanah dance or Dansa Tumbu Tana is a typical traditional dance of the Arfak ethnic group who live in Manokwari, West Papua. Tumbu Tanah dance is usually performed in important events, such as, welcoming guests from outside the Arfak community, victory in a battle, and wedding celebrations. This research aims to present a general description of Tumbu Tanah dance wich is also called the snake dance. The qualitative research qualitative drew the data from library research, observations, and available documents. This research shows that the main value found in Tumbu Tanah dance is that the Arfak community cannot live alone. This dance have to be performed by a number of people, at least by 10 persons. This indicates that in various activities they still need help from other people, both from their family and neighbors.